2012
DOI: 10.1103/physrevb.85.155444
|View full text |Cite
|
Sign up to set email alerts
|

Effects of edge potential on an armchair-graphene open boundary and nanoribbons

Abstract: Pseudospin flipping is found to be the key process leading to the formation of an edge-potential-induced edge state at an armchair-graphene open boundary and nanoribbons. At an open boundary, the edge potential U 0 is shown to turn on pseudospin-flipped (intravalley) scattering even though U 0 does not post an apparent breaking of the AB site (basis atoms) symmetry. For a valley-polarized incident beam, the interference between the pseudospin-conserving (intervalley) and -nonconserving (intravalley) processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 57 publications
(89 reference statements)
1
9
0
Order By: Relevance
“…After introducing an external on-site potential at the outermost sites, we find that the edge states are tunable. Interestingly, we find that the nature of such edge states is Tamm-like [19], in contrast with the equivalent model for the armchair graphene [8] but, as mentioned earlier, in agreement with the experiments in photonic lattices [17,18]. Furthermore, after introducing a Dzialozinskii-Moriya interaction (DMI), we find that the topologically protected edge states are sensitive to the presence of the Tamm-like states and they also become tunable.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…After introducing an external on-site potential at the outermost sites, we find that the edge states are tunable. Interestingly, we find that the nature of such edge states is Tamm-like [19], in contrast with the equivalent model for the armchair graphene [8] but, as mentioned earlier, in agreement with the experiments in photonic lattices [17,18]. Furthermore, after introducing a Dzialozinskii-Moriya interaction (DMI), we find that the topologically protected edge states are sensitive to the presence of the Tamm-like states and they also become tunable.…”
supporting
confidence: 90%
“…For example, there are flat edge states connecting the two Dirac points in a lattice with zig-zag [1] or bearded edges [6]. On the contrary, there are no edge states in a lattice with armchair boundary [7], unless a boundary potential is applied [8].…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17] The two nonequivalent valleys K and K points (Dirac points) at the corners of the Brillouin zone result from the triangular Bravias lattice, and the amplitudes of the states in the sublattice constitute a pseudospin. Various anomalous phenomena ranging from the Klein tunneling, 18 quantum Hall effects, 19,20 weak (anti-) localization, [21][22][23] focusing electron flow 24,25 electron beam supercollimation, 26 and edge-states physics [27][28][29][30][31][32] are attributed to the relativistic dispersion. Exploration of valleytronics in graphene has led to studies on valley filter, [33][34][35][36][37] valley polarization detection, 38 valley physics with broken inversion symmetry, 39 valley physics in strained graphene, 36,40,41 and valley-based qubit in graphene rings 42 and in double quantum dots.…”
Section: Introductionmentioning
confidence: 99%
“…But people found that modifications on armchair edges can induce complete flat bands, where the wavefunction has the character of valley polarization 27 . The use of edge potentials can also cause the formation of edge states, and the key is to turn on the pseudospin-flipped (intravalley) scattering processes 28 . In this case, the armchair edge bands behave similar to the zigzag ones.…”
Section: Introductionmentioning
confidence: 99%